Regulating the circular polarization in nitride-based light-emitting diodes through the spin injection - Wu, Yaping; Chen, Jiajun; Zhou, Jiangpeng; Lan, Jinshen; Zeng, Hao; He, Bing; Zhong, Zhibai; Guo, Jian; Song, Anke; Xia, Yuanzheng; Li, Xu; Wu, Zhiming; et al. (Applied physics express, 2019)
Circular polarization in nitride-based light-emitting diodes is investigated and regulated through the spin injection. Ferromagnet/dielectric are grown on n-type GaN as electron injector. Ultrathin quantum wells with quantum confinement effect are designed for enhancement of the circular polarizations in electroluminescence. By modulating the tunneling layer thickness and injection polarizer material, the preferred spin injection structure is determined. Room temperature circular polarization for surface-emission is optimized to 9.0% at most under a vertical magnetic field for the spin injecting contact. Spin relaxation time and diffusion length of about 34.9 ps and 134.5 nm, respectively, are revealed through the non-local three-terminal spin valve measurements.